AGE-STANDARDIZED INCIDENCE RATES FOR LEUKEMIA ASSOCIATED WITH CONSANGUINEOUS MARRIAGES IN 68 COUNTRIES, AN ECOLOGICAL STUDY - Mostafa Saadat (Mediterranean Journal of Hematology and Infectious Diseases)
Consanguineous marriage which defines as a union between biologically related persons has a variety of known deleterious correlations with factors that affect public health within human populations. To investigate the association between mean of inbreeding coefficient (a) and incidence of leukemia, the present ecological study on 67 countries was carried out. Statistical analysis showed that the age-standardized incidence rate of leukemia positively correlated with log10GNI per capita (r=0.693, df=65, P<0.001) and negatively correlated with log10a (r=-0.599, df=65, P<0.001). After controlling for log10GNI per capita, significant negative correlation between log10a and the age-standardized incidence rate of leukemia was observed (r=-0.386, df=64, P<0.001). The countries were stratified according to their GNI per capita, low and high income countries with GNI per capita less than and more than 10,000$, respectively. Statistical analysis showed that in high income countries, after controlling for log10GNI per capita, correlation between the age-standardized incidence rate of leukemia and log10a was still significant (r=-0.600, df=36, P<0.001). It should be noted that there was no significant association between the age-standardized mortality rate due to leukemia and log10a (P>0.05). The present finding indicating that the age-standardized for incidence rate of leukemia is lower in countries with high prevalence of consanguineous marriages.